High-performing heuristics to minimize flowtime in no-idle permutation flowshop. Issue 2 (1st February 2019) - Nagano, Marcelo Seido; Rossi, Fernando Luis; Martarelli, Nádia Junqueira
ABSTRACT: In this article, the issue of production scheduling in a no-idle flowshop environment is addressed. An extensive literature review has shown that there are no heuristics specifically proposed for this problem, especially when it comes to constructive heuristic methods. In this context, this article proposes a highly efficient simple constructive heuristic to minimize the total flowtime criterion. The proposed heuristic was embedded in the high performance iterated greedy algorithm. Computational results and statistical analysis show that the proposed heuristic overperformed the main constructive methods found up to now. In addition, it is observed that the integration of the proposed heuristic with the iterated greedy algorithm provides the most efficient metaheuristic for the problem.